DINAMIKA PERUBAHAN MINAT MENJADI GURU PADA MAHASISWA PROGRAM STUDI PENDIDIKAN - Anggitha Yuanistika; Didi Pramono (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The declining interest of younger generations in becoming teachers reflects a shift in perceptions of the profession, including among students of education study programs. This study aims to understand students’ perceptions of the teaching profession at Universitas Negeri Semarang, to examine changes in their interest during their studies, and to identify the factors influencing these changes. This research employs a descriptive qualitative approach. Data were collected through observation and interviews with eighth-semester students from various faculties at Universitas Negeri Semarang, and were then analyzed through data reduction, data display, and conclusion drawing. The findings show that students’ perceptions of the teaching profession are influenced by the important role of teachers in education, as well as various realities encountered in the field, such as heavy workloads, administrative demands, and inadequate welfare. Students’ interest in becoming teachers is also dynamic and may change during their studies, influenced by learning experiences, microteaching activities, Field Experience Practice (PPL), as well as family, social environment, and media. Based on Max Weber’s Theory of Social Action, students’ career choices are influenced by habitual, emotional, and rational considerations about their future. Interest in becoming a teacher may strengthen, change, or decline along with experiences during the educational process. ABSTRAK Menurunnya minat generasi muda untuk menjadi guru menunjukkan adanya perubahan cara pandang terhadap profesi tersebut, termasuk di kalangan mahasiswa program studi pendidikan. Penelitian ini bertujuan untuk memahami persepsi mahasiswa Universitas Negeri Semarang terhadap profesi guru, melihat perubahan minat selama perkuliahan, serta mengidentifikasi faktor-faktor yang mempengaruhinya. Penelitian ini menggunakan pendekatan kualitatif deskriptif. Data diperoleh melalui observasi dan wawancara terhadap mahasiswa semester delapan dari berbagai fakultas di Universitas Negeri Semarang, kemudian dianalisis melalui reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa pandangan mahasiswa terhadap profesi guru dipengaruhi oleh pentingnya peran guru dalam pendidikan, sekaligus berbagai realitas yang dihadapi di lapangan, seperti beban kerja, tuntutan administrasi, dan kesejahteraan yang belum memadai. Minat mahasiswa terhadap profesi guru juga bersifat dinamis dan dapat berubah selama perkuliahan, dipengaruhi oleh pengalaman belajar, kegiatan microteaching, Praktik Pengalaman Lapangan (PPL), serta faktor keluarga, lingkungan sosial, dan media. Berdasarkan Teori Tindakan Sosial Max Weber, pilihan karir mahasiswa dipengaruhi oleh kebiasaan, emosi, dan pertimbangan rasional tentang masa depan. Minat menjadi guru dapat menguat, berubah, atau menurun seiring pengalaman selama masa pendidikan.